Moderna: dividends, share buybacks, R&D, and shareholder value - McDonald, Michael (Henry Stewart Talks, 2024)
Pfizer vs. Moderna, How the COVID-19 crisis influenced Moderna, Capital use options, Share buybacks, R&D, Dividends, Moderna’s recent performance